Synthesis and Properties of Sulphonic Acid Type Polyurethane - Cong Liang, Cheng; Li, Ping; Hai Hu, Xian; Li, Weihao (Asian Journal of Chemistry, 2014)
In this paper, we reported a low cost and easy method for the preparation of sulphonic acid type polyurethane, which choose polyether polyol alcohol (PPG-1000), isophorone diisocyanate as the main raw material. By aliphatic diamine sulphonate, sulphonic acid groups was introduced to polyurethane chain, at the same time, polyurethane main chain was extended. Then the sulfonate type polyurethane emulsion was synthesized and solid content was 30 %. The products were characterized by means of FTIR and TG. Polyurethane emulsion had good storage stability and its film had good mechanical properties.